NEUROENDOCRINE TUMOR OF BLADDER - Muhammad Akram Malik; Sadia Hameed (Journal of University Medical & Dental College, 2012)
ABSTRACT Neuroendocrine tumor is a rare and aggressive tumor of urinary bladder with poor prognosis. It often presents late and the commonest presentation is haematuria. Cystectomy, partial cystectomy, TURBT with adjuvent radio/chemotherapy, radiotherapy or chemotherapy alone are various treatment options. We present a case of primary neuroendocrine tumor of urinary bladder in a 57 years old lady presented with haematuria. TURBT was performed and patient was reffered to oncology department for further management as she was not willing for cystectomy.